2010
DOI: 10.1104/pp.110.159145
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of CO2 and Light on the N2-Fixing Cyanobacterium Trichodesmium IMS101: Physiological Responses

Abstract: Recent studies on the diazotrophic cyanobacterium Trichodesmium erythraeum (IMS101) showed that increasing CO 2 partial pressure (pCO 2 ) enhances N 2 fixation and growth. Significant uncertainties remain as to the degree of the sensitivity to pCO 2 , its modification by other environmental factors, and underlying processes causing these responses. To address these questions, we examined the responses of Trichodesmium IMS101 grown under a matrix of low and high levels of pCO 2 (150 and 900 matm) and irradiance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
170
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(210 citation statements)
references
References 64 publications
(83 reference statements)
29
170
6
1
Order By: Relevance
“…Rates of N 2 fixation followed the diurnal pattern in nitrogenase abundance and its post-translational modification, with highest activities during midday (Berman-Frank et al 2001b;Levitan et al 2010aLevitan et al , 2007Milligan et al 2007). The timing of both, demodification of the iron protein and nitrogenase activity was shown to be affected by light intensities (Kranz et al 2010a;Zehr et al 1996). The described diurnal pattern in cell division, protein build-up and degradation, as well as physiological activity may represent a mean for Trichodesmium to optimize its energy budget.…”
Section: N 2 Fixationmentioning
confidence: 95%
See 4 more Smart Citations
“…Rates of N 2 fixation followed the diurnal pattern in nitrogenase abundance and its post-translational modification, with highest activities during midday (Berman-Frank et al 2001b;Levitan et al 2010aLevitan et al , 2007Milligan et al 2007). The timing of both, demodification of the iron protein and nitrogenase activity was shown to be affected by light intensities (Kranz et al 2010a;Zehr et al 1996). The described diurnal pattern in cell division, protein build-up and degradation, as well as physiological activity may represent a mean for Trichodesmium to optimize its energy budget.…”
Section: N 2 Fixationmentioning
confidence: 95%
“…The increase in N 2 fixation or PON production under elevated pCO 2 (Barcelos é Ramos et al 2007;Hutchins et al 2007;Kranz et al 2009;Levitan et al 2007) was found to be caused by a prolongation of the N 2 fixation period (Kranz et al 2010a). As these enhanced N 2 fixation rates were not accompanied by larger protein pools of nitrogenase (Levitan et al 2010b), they may have been achieved by post-translational modification and/or higher energy availability for nitrogenase activity.…”
Section: N 2 Fixationmentioning
confidence: 96%
See 3 more Smart Citations